2018
DOI: 10.3389/fpsyt.2018.00475
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Effect of Baclofen on Multiple Alcohol-Related Behaviors in Laboratory Animals

Abstract: This paper summarizes the several lines of experimental evidence demonstrating the ability of the prototypic GABAB receptor agonist, baclofen, to suppress multiple alcohol-related behaviors in laboratory rodents and non-human primates exposed to validated experimental models of alcohol use disorder (AUD). Specifically, treatment with baclofen has repeatedly been reported to suppress alcohol-induced locomotor stimulation, alcohol drinking (including binge- and relapse-like drinking), operant oral alcohol self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 73 publications
4
24
0
1
Order By: Relevance
“…Indeed, down-regulation of GAT-3 in rats showing addiction-like behaviours results in an increased GABAergic tone in the CeA, presumably as the result of decreased GABA clearance by these GABA transporters in the synaptic cleft 17 . Pharmacological activation of GABA B receptors by the agonist baclofen decreases the extracellular release of GABA 23,24 , and results in a dose-dependent decrease in alcohol intake at the population level, as shown in this and in previous studies 6 . Furthermore, as shown in the present study, baclofen selectively decreased the compulsive drinking of alcohol by AAR rats when challenged by adulteration with quinine.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Indeed, down-regulation of GAT-3 in rats showing addiction-like behaviours results in an increased GABAergic tone in the CeA, presumably as the result of decreased GABA clearance by these GABA transporters in the synaptic cleft 17 . Pharmacological activation of GABA B receptors by the agonist baclofen decreases the extracellular release of GABA 23,24 , and results in a dose-dependent decrease in alcohol intake at the population level, as shown in this and in previous studies 6 . Furthermore, as shown in the present study, baclofen selectively decreased the compulsive drinking of alcohol by AAR rats when challenged by adulteration with quinine.…”
Section: Discussionsupporting
confidence: 85%
“…Many preclinical and clinical studies have highlighted the important involvement of the gamma-aminobutyric acid (GABA) system in the regulation of the reinforcing properties of alcohol and in the development of AUD. Pharmacological manipulations of GABAergic transmission through targeting both GABA A and GABA B receptors, influence different behavioural responses to alcohol, including alcohol self-administration, voluntary alcohol drinking, relapse-like and binge-like alcohol drinking, and the motivation for alcohol [6][7][8][9][10] . Furthermore, alterations in the expression of genes encoding some GABA A and GABA B receptor subunits, as well as GABA transporters, have been shown to influence the predisposition to high alcohol consumption and vulnerability to AUD in humans, as well as AUD-like behaviour in rodents 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide use of baclofen as a myorelaxant has provided detailed information on its safety and side effects in these patients (17). From the 1970s, research, largely in animal addiction models, suggested that baclofen may also be effective in the treatment of AUD (1).…”
Section: Review Of the Current Research Evidence And Clinical Experiencementioning
confidence: 99%
“…After promising preclinical evidence [for review see Colombo and Gessa (1)], clinical studies started to investigate whether baclofen may be useful in the treatment of alcohol use disorder (AUD). However, to date, clinical studies have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%